Utilizing Small Telescopes Operated by Citizen Scientists for Transiting Exoplanet Follow-up. (8th April 2020) - Zellem, Robert T.; Pearson, Kyle A.; Blaser, Ethan; Fowler, Martin; Ciardi, David R.; Biferno, Anya; Massey, Bob; Marchis, Franck; Baer, Robert; Ball, Conley; Chasin, Mike; Conley, Mike; et al.
Abstract: Due to the efforts by numerous ground-based surveys and NASA's Kepler and Transiting Exoplanet Survey Satellite (TESS), there will be hundreds, if not thousands, of transiting exoplanets ideal for atmospheric characterization via spectroscopy with large platforms such as James Webb Space Telescope and ARIEL. However their next predicted mid-transit time could become so increasingly uncertain over time that significant overhead would be required to ensure the detection of the entire transit. As a result, follow-up observations to characterize these exoplanetary atmospheres would require less-efficient use of an observatory's time—which is an issue for large platforms where minimizing observing overheads is a necessity. Here we demonstrate the power of citizen scientists operating smaller observatories (≤1 m) to keep ephemerides "fresh, " defined here as when the 1 σ uncertainty in the mid-transit time is less than half the transit duration. We advocate for the creation of a community-wide effort to perform ephemeris maintenance on transiting exoplanets by citizen scientists. Such observations can be conducted with even a 6 inch telescope, which has the potential to save up to ∼10, 000 days for a 1000-planet survey. Based on a preliminary analysis of 14 transits from a single 6 inch MicroObservatory telescope, we empirically estimate the ability of small telescopes to benefit the community. Observations with a small-telescope network operated by citizen scientists are capable of resolving stellar blends to within 5″/pixel, can follow-up long period transits in short-baseline TESS fields, monitor epoch-to-epoch stellar variability at a precision 0.67% ± 0.12% for a 11.3 V -mag star, and search for new planets or constrain the masses of known planets with transit timing variations greater than two minutes.